2020
DOI: 10.3329/ajmbr.v6i3.49794
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of multiple drug-resistant bacteria from the waste of hospital and non-hospital environment

Abstract: Antibiotics used in hospitals for patient care which potentially growing antibiotic resistant bacteria in hospital waste and simultaneously transmitting to non-hospital environments by drainage system. Total 20 samples were collected randomly and examined with different bacteriological, biochemical and molecular tests. 55 bacterial isolates were isolated from all samples, among them 32 (58.2%) were from hospital environment and 23 (42.1%) were from non-hospital environment. The result of total viable count sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
2
3
2
Order By: Relevance
“…According to a study conducted in India, the incidence of antibiotic resistance was found to a maximum of 73.9% of strains were resistant to ampicillin followed by nalidixic acid (72.5%), penicillin (63.8%), co-trimoxazole (55.1%), and resistance to streptomycin, chloramphenicol, nitrofurantoin, tetracycline, and doxycycline was recorded in less than 13% of the strains 37 which disagree with the present results. The current result also disagrees with results reported by Alam et al, 37 Moges et al 10 and Hasan et al 27 reported that most isolates were resistant to ampicillin. The probable reason for this difference may be the type of antibiotic used to test antibiotic susceptibility, the type of bacterial isolates tested, and the antibiotic used in the study areas.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to a study conducted in India, the incidence of antibiotic resistance was found to a maximum of 73.9% of strains were resistant to ampicillin followed by nalidixic acid (72.5%), penicillin (63.8%), co-trimoxazole (55.1%), and resistance to streptomycin, chloramphenicol, nitrofurantoin, tetracycline, and doxycycline was recorded in less than 13% of the strains 37 which disagree with the present results. The current result also disagrees with results reported by Alam et al, 37 Moges et al 10 and Hasan et al 27 reported that most isolates were resistant to ampicillin. The probable reason for this difference may be the type of antibiotic used to test antibiotic susceptibility, the type of bacterial isolates tested, and the antibiotic used in the study areas.…”
Section: Discussioncontrasting
confidence: 99%
“…(11.5%), and S. aureus (8.2%). A similar study conducted by Hasan et al 27 reported that the most frequently isolated bacteria were E. coli (29%), followed by Pseudomonas spp. (21.8%), and Klebsiella spp.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, none of the gram-negative isolates showed resistance against ciprofloxacin. This was different from other studies that have been performed in Bangladesh (Hasan et al, 2020). Among Gram-positive bacterial isolates, the most striking multiple drug-resistant isolates, which were resistant to 4 antibiotics, was B. cereus (isolate-2) followed by L. macroides (isolate-4).…”
Section: Antibiotics Susceptibility Profiling Of Isolated Bacteriacontrasting
confidence: 85%
“…Low resistance rates of 35% and 34% to ertapenem and meropenem, which contradicts our findings, have been reported elsewhere in South Africa [37]. The susceptibility rate against fluoroquinolones (ciprofloxacin 79.3% and norfloxacin 86.2%) and Nitrofurans (Nitrofurantoin 71.7%) is similar to another report [10]. In this study, aminoglycosides (amikacin and gentamicin) exhibited a high susceptibility rate, in line with an earlier study [38].…”
Section: Discussionsupporting
confidence: 74%
“…Multidrug-resistant pathogenic bacteria significantly impact hospitalacquired infection [9]. Modern medicine faces the challenge of increased antibiotic resistance [10]. The therapeutic action of antibiotics against K. pneumoniae has been proven abortive due to the development of resistance [11].…”
Section: Introductionmentioning
confidence: 99%